Exploring Challenges In The Adoption And Implementation Of The E-NAM Platform In Indian Agricultural Marketing (Journal of Namibian Studies : History Politics Culture, 2022)
This paper scrutinizes the challenges hindering the widespread adoption and effective implementation of India's e-NAM platform in agricultural marketing. It addresses persistent issues in post-harvest marketing impacting farmers and the economy. Despite its transformative potential, the e-NAM platform's success hinges on farmer acceptance. The comprehensive literature review emphasizes the platform's intentions, desired outcomes, and the shift from traditional to digital agricultural trading. Methodologically, the study employs surveys and qualitative insights, analyzing data from Haryana. Findings highlight critical challenges: farmers' lack of digital literacy and awareness, infrastructural limitations, trust issues, institutional complexities, and perceived risks. Statistical analyses confirm the study's reliability and validity. The discussion outlines practical implications, advocating for digital literacy programs, infrastructure enhancements, trust-building measures, and institutional streamlining. The study's theoretical contributions provide a robust framework for future research, emphasizing the need for collaborative efforts to transform India's agricultural marketing via e-NAM.